Synergistic pathological effect of Mycoplasma gallisepticum with Ornithobacterium rhinotracheale infection in layer chicken - SIVASEELAN, S; BALACHANDRAN, P; BALASUBRAMANIAM, G; MADHESWARAN, R (The Indian Journal of Animal Sciences, 2015)
Synergistic pathological effect of Mycoplasma gallisepticum (MG) with Ornithobacterium rhinotracheale (ORT) infection in layer chicken was evaluated in 70 commercial layer chicken farms. Ornithobacterium rhinotracheale organism was confirmed by its growth characteristics on agar media and typical morphology on Gram’s staining. Polymerase chain reaction technique was used for the confirmation of Mycoplasma gallisepticum. Other concurrent respiratory viral infections like Newcastle disease and infectious bronchitis were ruled out by hemaggutination and inhibition tests and bacterial diseases like colibacillosis, pasteurellosis and infectious coryza were ruled out by culture and staining techniques. The severity of clinical signs, gross pathology and histopathology increased in combined cases of MG and ORT than individual occurrence of these diseases. Zero and 7.8% mean mortality rate were observed in ORT and MG infections respectively, whereas 15% mean mortality rate was recorded in the combined cases. The synergistic increase in mortality rate of MG with ORT was clearly supported by the gross and histopathological alterations.